Early Labor Market Origins of Long-Term Mental Health and its Intergenerational Correlation - Micole De Vera; Javier Garcia-Brazales; Jiayi Lin (ZBW - Leibniz Information Centre for Economics, 2022)
What drives long-term mental health and its intergenerational correlation? Exploiting variation in unemployment rates upon labor market entry across Australian states and cohorts, we provide novel evidence of persistent effects on mental health two decades after labor market entry. We find that individuals exposed to a one percentage point higher unemployment rate at labor market entry relative to trend have 14% of a standard deviation worse mental health at ages 36–40. We further document an intergenerational impact of labor market entry conditions. Along the extensive margin, females more impacted by labor market entry conditions in terms of mental health increase completed fertility. Along the intensive margin, daughters whose parents experienced a one percentage point higher unemployment rate at entry have 18% of a standard deviation worse mental health during adolescence. Sons' mental health is not impacted.
Keywords: E32; I14; J13; 330; Recession; Mental health; Well-being; Intergenerational correlation; Australia